Frequency and correlates of non-adherence in a large sample of adult patients after kidney transplantation: A cross-sectional KTx360° substudy - Nöhre, Mariel; Klewitz, Felix; Bauer-Hohmann, Maximilian; Kyaw Tha Tun, Eva; Lieb, Marietta; Erim, Yesim; Tegtbur, Uwe; Schiffer, Lena; Pape, Lars; Schiffer, Mario; de Zwaan, Martina (Journal of Psychosomatic Research, 2026)
Objective Non-adherence to immunosuppressive medication (ISM) is a common and preventable cause of graft loss after kidney transplantation (KTx). Adherence is a multifaceted construct influenced by various factors. Despite frequent reports linking non-adherence with multiple variables, results often seem contradictory. The lack of patient registers in Germany to encompass psychosocial aspects limits data to smaller, selective studies. The aim was to evaluate the frequency and correlates of non-adherence in a large sample of adult KTx patients. Methods This cross-sectional substudy was embedded within the structured follow-up program KTx360°. It took place at the transplant centers of Hannover Medical School, Hann. Münden and Erlangen in Germany between May 2017 and October 2020. 838 adult KTx patients participated in this substudy. Adherence was assessed using the Basel Assessment of Adherence to Immunosuppressive Medications Scale (BAASIS) alongside other sociodemographic, psychosocial, and medical variables. Results Participants had an average age of 52.3 years (SD = 13.5), with 58.7 % male. According to the BAASIS interview, 22.1 % reported non-adherence, mainly due to timing (13.0 %) and taking (11.7 %) non-adherence, with only 0.5 % ceasing at least one ISM. Factors linked to non-adherence in regression analysis included younger age, male gender, longer post-transplant time, and perceived medication overuse. The effect sizes were small. The informative value is limited by the design and the sample size. Conclusion In our cross-sectional analysis, nearly a quarter of the participants reported suboptimal adherence, mainly associated with primarily non-modifiable risk factors. Routine adherence assessments and targeted interventions are essential to improving long-term outcomes.
CRIS-Team Scopus Importer:2025-12-19
Keywords: Adherence; Compliance; Kidney transplant; Psychosocial care; Renal transplant